Kepatuhan WPOP Usahawan Sebelum dan Sesudah Kebijakan Tax Amnesty Di KPP Pratama Jakarta Pancoran - Dona Fitria; Ismail Dwi Cahyo (STIE Mandala Jember, 2019)
The purpose of this study was to determine and analyze the WPOP Business compliance before and after the tax amnesty was implemented at KPP Pratama Jakarta Pancoran. The data analysis technique in this study uses the 2016 - 2017 SPT tax compliance ratio. Statistical tests using the Paried Sample t-Test. The results showed that the number of WPOP business compliance ratios on time after the enactment of the tax amnesty increased by 4.64%, in 2016 amounting to 9.12% and in 2017 amounting to 13.76%. The number of Business WPOPs that report annual SPT not on time after the enactment of the tax amnesty has decreased from 577 to 164. The results of the WPOP Business Compliance ratio not on time after the enactment of the tax amnesty dropped from 2016 by 6.97% to only 1.91% in in 2017. However, the number of Business WPOPs that did not report Annual Tax Returns after the enactment of the tax amnesty increased from 2016 to 6,922 to 7,238 in 2017. The ratio of taxpayer compliance that does not submit Annual Tax Returns increases 0.43%.The statistical results using a different paired test can be concluded that there is no difference in compliance of the WPOP Entrepreneurs before and after the enactment of the Tax Amnesty at the Pancoran Primary Tax Office. It means that the Directorate General of Taxes has not succeeded in increasing the compliance of the Business WPOP through the Tax Amnesty policy regulations.